Literature craft and voice - Delbanco, Nicholas. (McGraw-Hill, 2010)
Reading a poem in its elements; Going further with reading; Writing about poetry; Words; Voice: tone, persona, and irony; Imagery and symbol; Figures of speech; Sound, rhyme and rhythm...